Hormonal responses and adaptations to resistance exercise and training - Kraemer, W. J.; Ratamess, N. A. (Sports Medicine, 2005)
Resistance exercise has been shown to elicit a significant acute hormonal response. It appears that this acute response is more critical to tissue growth and remodelling than chronic changes in resting hormonal concentrations, as many studies have not shown a significant change during resistance training despite increases in muscle strength and hypertrophy. Anabolic hormones such as testosterone and the superfamily of growth hormones (GH) have been shown to be elevated during 15-30 minutes of post-resistance exercise providing an adequate stimulus is present. Protocols high in volume, moderate to high in intensity, using short rest intervals and stressing a large muscle mass, tend to produce the greatest acute hormonal elevations (e.g. testosterone, GH and the catabolic hormone cortisol) compared with low-volume, high-intensity protocols using long rest intervals. Other anabolic hormones such as insulin and insulin-like growth factor-1 (IGF-1) are critical to skeletal muscle growth. Insulin is regulated by blood glucose and amino acid levels. However, circulating IGF-1 elevations have been reported following resistance exercise presumably in response to GH-stimulated hepatic secretion. Recent evidence indicates that muscle isoforms of IGF-1 may play a substantial role in tissue remodelling via up-regulation by mechanical signalling (i.e. increased gene expression resulting from stretch and tension to the muscle cytoskeleton leading to greater protein synthesis rates). Acute elevations in catecholamines are critical to optimal force production and energy liberation during resistance exercise. More recent research has shown the importance of acute hormonal elevations and mechanical stimuli for subsequent up- and down-regulation of cytoplasmic steroid receptors needed to mediate the hormonal effects. Other factors such as nutrition, overtraining, detraining and circadian patterns of hormone secretion are critical to examining the hormonal responses and adaptations to resistance training.